Colonization of murine ganglia by a superinfecting strain of herpes simplex virus. - Meignier, B (1983)
We report on the colonization of murine trigeminal ganglia after sequential infection of mice by herpes simplex viruses (HSVs). In preliminary studies, we have established that whereas the HSV-1(F) strain efficiently colonizes ganglia when inoculated by either the ear or eye routes, the HSV-1 X HSV-2 recombinant C7D colonizes ganglia when inoculated by the eye route only. The experimental design consisted of inoculating the right eye with C7D on day 1 and with HSV-1(F) in both left and right eyes on day 26. Both right and left trigeminal ganglia were removed and analyzed independently for latent virus on day 52. Our studies indicate that HSV-1(F) viruses were recovered from all left trigeminal ganglia but from only a small number of right trigeminal ganglia. Some right trigeminal ganglia yielded no viruses, whereas others yielded both C7D and HSV-1(F) viruses identified on the basis of plaque morphology and restriction enzyme cleavage patterns of viral DNA. The results indicate that more than one virus may colonize the same ganglion and that trigeminal ganglia may be protected from colonization by a superinfecting virus by determinants acting at a local level in the absence of demonstrable virus.